First, we have to convert our function (of x) into a function of y (we revolve the curve around the y-axis). So:

And the derivative of x:

Now, we can calculate the area of the surface:

We could calculate this integral (not very hard, but long), or use
(1),
(2) and
(3) to get:



Calculate indefinite integral:

And the area:
![A=2\pi\int\limits_0^{10}x\sqrt{4x^2+1}\,dx=2\pi\cdot\dfrac{1}{12}\bigg[\left(4x^2+1\right)^\frac{3}{2}\bigg]_0^{10}=\\\\\\= \dfrac{\pi}{6}\left[\big(4\cdot10^2+1\big)^\frac{3}{2}-\big(4\cdot0^2+1\big)^\frac{3}{2}\right]=\dfrac{\pi}{6}\Big(\big401^\frac{3}{2}-1^\frac{3}{2}\Big)=\boxed{\dfrac{401^\frac{3}{2}-1}{6}\pi}](https://tex.z-dn.net/?f=A%3D2%5Cpi%5Cint%5Climits_0%5E%7B10%7Dx%5Csqrt%7B4x%5E2%2B1%7D%5C%2Cdx%3D2%5Cpi%5Ccdot%5Cdfrac%7B1%7D%7B12%7D%5Cbigg%5B%5Cleft%284x%5E2%2B1%5Cright%29%5E%5Cfrac%7B3%7D%7B2%7D%5Cbigg%5D_0%5E%7B10%7D%3D%5C%5C%5C%5C%5C%5C%3D%20%5Cdfrac%7B%5Cpi%7D%7B6%7D%5Cleft%5B%5Cbig%284%5Ccdot10%5E2%2B1%5Cbig%29%5E%5Cfrac%7B3%7D%7B2%7D-%5Cbig%284%5Ccdot0%5E2%2B1%5Cbig%29%5E%5Cfrac%7B3%7D%7B2%7D%5Cright%5D%3D%5Cdfrac%7B%5Cpi%7D%7B6%7D%5CBig%28%5Cbig401%5E%5Cfrac%7B3%7D%7B2%7D-1%5E%5Cfrac%7B3%7D%7B2%7D%5CBig%29%3D%5Cboxed%7B%5Cdfrac%7B401%5E%5Cfrac%7B3%7D%7B2%7D-1%7D%7B6%7D%5Cpi%7D)
Answer D.
Solutions
Factor <span>3x</span>²<span><span>−2x−8</span><span>
</span></span>1. Multiply 3 by -8, which is -24.
2. Ask: Which two numbers add up to -2 and multiply to -24?
3. Answer: 4 and -6
4. Rewrite <span>−2x </span>as the sum of <span>4x </span>and <span>−6x</span>:

<span>
</span><span>Factor out common terms in the first two terms, then in the last two terms
</span>
Factor out the common term <span>3x+4
</span>
Solve for <span>x
</span>1. Ask: When will <span>(3x+4)(x−2) </span>equal zero?
2. Answer: When <span>3x+4=0 </span>or <span>x−2=0.</span>
3. Solve each of the 2 equations above:
x = −<span>4 / 3</span>,<span>2</span>
<span>3x + x - 13 + 4 - 6x =12
Combine like terms....
- 2x - 9 =12
Add 9 to both sides....
-2x = 21
Divide both sides by -2 to get x by its self....
x = -21/2</span>
Answer:
10
Step-by-step explanation:
sadasdasdasd
You've got

just sub the number of the term to findd the term
first term is A(1)=-2(5)^(1-1)=-2(5)^0=-2(1)=-2
4th is A(4)=-2(5)^(4-1)=-2(5)^3=-2(125)=-250
8th term is A(8)=-2(5)^(8-1)=-2(5)^7=-2(78125)=-156250